Health and safety in welding and allied processes. - Blunt, Jane (CRC Press ; Woodhead Pub., 2002)
This edition of Health and safety in welding and allied processes has been extensively revised to take into recent account advances in technology and legislative changes both in the UK and USA. Beginning with a description of the core safety requirements, it goes on to describe the special hazards found in the welding environment - noise, radiation, fume, gases and so on in terms of their effects and the strategies that can be adopted to avoid them. The book takes each major joining technology in turn and discusses the key hazards that are most relevant to each process. There are chapters covering: the common arc and gas welding processes; specialised welding processes; brazing, soldering and thermal spraying; welding and flame spraying of plastics; radiographic inspection; mechanical hazards; noise and vibration; radiation; compressed gases; fume and ventilation; fire and first aid; and welding in situations of increased hazard, such as those requiring special precautions to ensure safe working on vessels contaminated by flammable materials. The aim throughout the book is to explain the hazards clearly and concisely, describe how they arise, and suggest practical methods to achieve safe working. Health and safety in welding and allied processes is an essential resource for welders, their managers and all health and safety practitioners who have welding and related processes taking place in their workplaces. A completely revised new edition of the definitive work on welding health and safetyProvides detailed risk analysis for all the major processesShows how to set up effective workplace systems for risk assessment, first aid and reporting.
Keywords: Welding -- Health aspects.; Welding -- Safety measures.; elektronické knihy; electronic books